Evaluasi Kondisi dan Kinerja Fisik Bangunan Jaringan Irigasi Lang-Lang, Kabupaten Malang - Joko Sunarbowo; Yurnalisdel Yurnalisdel; Galih Damar Pandulu (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
The Lang-Lang Irrigation Network (JI), located in Singosari Subdistrict, Malang Regency, plays a vital role in supporting the productivity of 98 hectares of agricultural land. The Lang-Lang Irrigation Network (JI) is one of 717 irrigation networks (JI) in Malang Regency. Geographically, the service area of the Lang-Lang Irrigation Network (JI) is highly complex as it stretches from Ngenep Village to Lang-Lang Village, traversing an area with a mix of dense settlements and agricultural land. These conditions create the potential for dual pressures on the irrigation network: technical challenges in maintaining efficient gravity flow, and non-technical challenges in the form of potential disruptions (such as trash dumping or illegal tapping) due to proximity to densely populated settlements. The survey design for the irrigation system performance assessment analysis is based on Ministry of Public Works and Public Housing Regulation No. 12/PRT/M/2015. The analysis process integrates qualitative findings from field inspections with quantitative calculations using the Irrigation Structure Performance Index. The analysis results indicate that, in general, the infrastructure along the 500-meter-long Lang-Lang JI primary channel is in a state of Minor Damage (RR), with a physical assessment weight of 82.50%, and 17.50% falls into the category requiring periodic maintenance of a preventive nature. Meanwhile, the results of the assessment of the physical condition of irrigation infrastructure—specifically control and auxiliary structures—show that 74.44% are in a state of moderate damage (MD), and 25.56% fall into the category requiring periodic maintenance in the form of repairs.